The The Influence of Training and Competence on Crew Readiness in Using Fire Extinguishers and Its Impact on Ship Safety at Bourbon Offshore Greenmar Company - Dani Sitorus, Very; Herawati, Aty (Dinasti Publisher, 2025)
Fire is one of the disasters that often occurs, especially in sea transportation. Based on data from the National Transportation Safety Committee 2024, although there was a decline in 2018-2020, it then experienced a slight increase again in 2021-2023. Fires that occur on ships can occur due to unpreparedness and negligence of the ship's crew or can also be caused by other factors. This study aims to analyze the factors that influence the readiness of the crew in the use of fire extinguishers, namely whether there is an effect of training on the readiness of the crew in the use of fire extinguishers, whether there is an effect of competence on the readiness of the crew in the use of fire extinguishers and the readiness of the crew in the use of fire extinguishers affects ship safety. The study was conducted at the Bourbon Offshore Greenmar company with a sample of 84 crew members taken by convenience. Data collection was carried out by distributing questionnaires with a Likert scale. Data analysis carried out in addition to descriptive analysis, also carried out partial least square analysis to see valid indicators that can be used to measure variables, see the relationship model between existing variables. The results of the analysis show that there is an influence of training on the readiness of the crew in using fire equipment and there is an influence of competence on the readiness of the crew in using fire equipment where the readiness of the crew in using fire equipment will have an impact on ship safety.